ANALYSIS MODELS OF PROFITABILITY IN AGRICULTURE - S. Bumbescu (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In this article there is developed a synthetic theoretical framework regarding the profitability analysis through economic and financial rates of return using different models, and also it is made a case study on the similarities and differences between various models of rates of return analysis in agriculture. The motivation of choosing this theme is to determine the relationship between financial and economic profitability using Pearson correlation coefficient. The research conducted leads to two main categories of results; on the one hand there is made a qualitative theoretical synthesis on the rates of return in models, on the other hand it is determined the correlation between financial and economic profitability in the agriculture organizations.